Governance of Assisted Living in Singapore: Lessons for Aging Countries - Tan, Si Ying; Poh, Luting; Lim, Jeremy (Frontiers in Public Health, 2022)
A global trend toward aging populations means that the challenge of providing adequate long-term care to older people looms large in many countries. In Singapore, a public discourse revolving around the expansion of assisted living to create age-friendly environments in long-term care has emerged. This study examines Singapore's experience in developing regulations for assisted living by documenting the different levels of regulation in place and by identifying the regulatory gaps remaining to govern assisted living. Anchoring in a conceptual framework on the governance of assisted living, different regulatory components of assisted living at the micro-, meso-, and macro-levels are analyzed. Using a case study method, primary and secondary data examining the experiences of governing and implementing assisted living in Singapore were collected. Analysis was conducted using a thematic analysis approach. Micro- and some macro-level regulations, which include admission assessment, staffing, and infrastructural requirements for assisted living, are maturing and evolving, while meso-level regulations, such as operational management, the monitoring framework, and stipulations for training requirements for staff, remain a work-in-progress in Singapore. The regulations for assisted living are currently primarily guided by soft laws, such as practice guidelines; the government has committed toward enacting permanent regulations for all long-term care facilities with the phased implementation of the Health Care Services Act from 2021 to 2023. We conclude that assisted living, despite the early stage of its development in Singapore, is a viable care model that should be expanded to meet the rising demand for care on the part of a majority of older people, who fall in the middle of the care continuum (that is, they can neither live independently nor need complete institutionalization). We also propose five policy recommendations for all aging countries to strengthen the governance of assisted living in long-term care. These include establishing (i) clear provisions on care quality assessment and the redress of grievance, (ii) minimum standards of care, (iii) differential regulations for assisted living, (iv) routine care assessment, and, (v) applying technology in assisted living facilities to address a shortage of care workers.